2021
DOI: 10.1212/wnl.0000000000012074
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Medical Diagnoses Preceding the First Diagnosis of Multiple Sclerosis

Abstract: ObjectiveTo explore the occurrence of diseases and symptoms in the 5 years before diagnosis in patients with multiple sclerosis (MS) in a case-control study.MethodsUsing ambulatory claims data, we systematically assessed differences in the occurrence of diseases and symptoms in the 5 years before first diagnosis in patients with MS (n = 10,262) compared to patients with 2 other autoimmune diseases, Crohn disease (n = 15,502) and psoriasis (n = 98,432), and individuals without these diseases (n = 73,430).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
(44 reference statements)
1
28
1
Order By: Relevance
“…Firstly, we confirmed previous findings identifying a list of different symptoms more frequently encountered in the preclinical period before MS onset compared to the general population [1,2,8]. They included headaches, ophthalmic, musculoskeletal, cardiovascular, digestive, urinary, laryngological, and mental complaints.…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, we confirmed previous findings identifying a list of different symptoms more frequently encountered in the preclinical period before MS onset compared to the general population [1,2,8]. They included headaches, ophthalmic, musculoskeletal, cardiovascular, digestive, urinary, laryngological, and mental complaints.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, evidence has emerged of a measurable, symptomatic phase of MS that precedes the classic understanding of MS disease onset, a period known as a prodrome (1). Several studies have found increased total and condition-specific health-care utilization in the years preceding MS onset and diagnosis (1)(2)(3)(4)(5)(6). Biological changes are also evident during this period, including higher serum neurofilament light levels up to 6 years before MS symptom onset (vs. matched persons without MS) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies raised the hypothesis of the existence of a prodromal phase of MS. 17 19 In our previous study, however, we found evidence for demyelinating events explaining the observed increased use of the healthcare system of patients with MS in the years before diagnosis. 13 The characteristics and the duration of a hypothesized prodromal phase of MS are currently unknown. While our results suggest that the association of pregnancies and MS risk precede the disease or a phase with ongoing but undiagnosed disease, we cannot fully exclude the possibility that a prodromal phase with yet-to-be-defined clinical features might have an effect on pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we observed higher recording rates for 43 ICD-10 codes for patients with MS as compared to controls in the 5 years before diagnosis. 13 Many of these are neurological or neurovascular ICD-10 codes or correspond to symptoms that could represent demyelinating events. We, therefore, performed a sensitivity analysis where we removed women with recorded neurological or neurovascular ICD-10 codes or codes suggestive of demyelinating events and associated with MS in our previous study 13 in the 5 years before diagnosis ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%